Coordination of mitophagy and mitochondrial biogenesis during ageing in C. elegans - Palikaras, K.; Lionaki, E.; Tavernarakis, N. (Nature, 2015)
Impaired mitochondrial maintenance in disparate cell types is a shared hallmark of many human pathologies and ageing. How mitochondrial biogenesis coordinates with the removal of damaged or superfluous mitochondria to maintain cellular homeostasis is not well understood. Here we show that mitophagy, a selective type of autophagy targeting mitochondria for degradation, interfaces with mitochondrial biogenesis to regulate mitochondrial content and longevity in Caenorhabditis elegans. We find that DCT-1 is a key mediator of mitophagy and longevity assurance under conditions of stress in C. elegans. Impairment of mitophagy compromises stress resistance and triggers mitochondrial retrograde signalling through the SKN-1 transcription factor that regulates both mitochondrial biogenesis genes and mitophagy by enhancing DCT-1 expression. Our findings reveal a homeostatic feedback loop that integrates metabolic signals to coordinate the biogenesis and turnover of mitochondria. Uncoupling of these two processes during ageing contributes to overproliferation of damaged mitochondria and decline of cellular function.
Palikaras, KonstantinosLionaki, EiriniTavernarakis, NektariosengResearch Support, Non-U.S. Gov'tEnglandNature. 2015 May 28;521(7553):525-8. doi: 10.1038/nature14300. Epub 2015 Apr 20.
Keywords: *Mitophagy/genetics; Aging/pathology/*physiology; Animals; Caenorhabditis elegans Proteins/metabolism; Caenorhabditis elegans/*cytology/genetics/*physiology; Carrier Proteins; DNA-Binding Proteins/metabolism; homeostasis; Insulin-Like Growth Factor I/metabolism; Insulin/metabolism; Longevity; Membrane Proteins/metabolism; Mitochondria/genetics/*metabolism/pathology; signal transduction; Stress, Physiological; Transcription Factors/metabolism